Consciousness Energy Healing Treatment: Impact on the Physicochemical and Thermal Characteristics of Folic Acid - Nayak, Gopal; Kumar Trivedi, Mahendra; Branton, Alice; Trivedi, Dahryn; Jana, Snehasis (International Journal of Nutrition, 2018)
Folic acid is essential in the body for the production of DNA and also plays various vital functions within the body. This study on folic acid was done to analyze the results of the Trivedi Effect® on its physicochemical and thermal properties with the help of analytical techniques. The method involves dividing the test sample into two parts. The first part was termed as a control sample, and no treatment was given to it; while the second part received the Biofield Energy Treatment remotely by a renowned Biofield Energy Healer, Gopal Nayak and termed as the treated sample. The study revealed that the particle sizes reduced by 7.01% (d10), 6.53% (d50), 8.37% (d90), and 15.99% {D(4,3)}, thus increased the surface area by 1.72%, in the treated sample compared with the control sample. The PXRD data showed changes in the peak intensities and crystallite sizes ranging from -36.81% to 113.41% and -15.79% to 318%, respectively, thus increased in the average crystallite size by 22.55% of the treated sample compared with the control sample. The TGA analysis of the treated sample revealed a 3.94% increase in total weight loss that resulted in the remarkable reduction in the residual amount by 14.99%, in comparison to the untreated sample. The latent heat of fusion (ΔHfusion) and latent heat of decomposition (ΔHdegradation) were significantly altered by -10.33% and 10.46%, respectively in the treated sample compared to the untreated sample. The study denoted that the Biofield Energy Treatment is a novel approach that could be used to develop some polymorph of folic acid and that might improve its solubility, dissolution, and bioavailability in comparison to the control sample. Hence, the treated folic acid in the nutraceutical/pharmaceutical formulations might be useful concerning better drug performance and efficacy.
Keywords: Folic Acid; Particle Size; Surface Area; Powder X-Ray Diffraction (PXRD); Differential Scanning Calorimetry (DSC); Thermal Properties